IDENTIFIKASI PERAN PENYULUH PERTANIAN DAN KAPASITAS PETANI DALAM BUDIDAYA PADI SAWAH DI KELURAHAN WAKANGKA KECAMATAN KAPONTORI KABUPATEN BUTON - Leni Nurfila; Dasmin Sidu; Mardin (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2025)
The objective of this study was to ascertain the role of agricultural extension workers and the capacity of wet-rice farmers in Wakangka Village, Kapontori District, Buton Regency. The population of this study comprised 140 rice paddy farmers, with a sample size of 58 individuals determined by the Slovin formula with an error rate of 10%. The sampling method employed in this research is simple random sampling. The present study employs a quantitative approach. The data were collected using a variety of research methods, including survey techniques, observation, interviews, and documentation. The media was used to disseminate the questionnaires. The research variables consisted of the role of agricultural extension workers (role of educator, information dissemination, facilitator, consultant, supervisor, monitoring and evaluator) and the capacity of farmers in paddy rice cultivation (managerial, technical, and social capacity). A descriptive analysis was employed to ascertain the role of agricultural extension workers and the capacity of farmers in wetland rice cultivation. The results indicated that the role of agricultural extension officers in the cultivation of paddy rice in Wakangka Village, Kapontori Sub-district, Buton Regency is multifaceted. These officers have performed a variety of roles, including educators, information disseminators, facilitators, consultants, supervisors, monitors, and evaluators. However, the predominant role of extension officers is that of educators. Rice paddy farmers in Wakangka Village have demonstrated competencies in management, technology, and society. However, the management capacity of these farmers is found to be deficient, whereas their technological and societal capacities have surpassed 50%.